Floating sulphur biofilms structure, function and biotechnology - Molwantwa, Jennifer Balatedi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
Mine wastewaters generated during active production operations, and decanting streams following mine closure have major environmental impacts, and volumes requiring treatment are expected to increase substantially as the South African mining industry matures. Biological treatment of mine waters has been the subject of increasing interest, where sulphate reducing bacteria are employed for the reduction of sulphate to sulphide, precipitation of metals and the production of alkalinity. However, the sulphide if not removed from the system can be oxidised back to sulphate. As a result there have been limitations especially in the provision of technological options that are sustainable over the long-term, where the total sulphur (in its different forms) can be removed from the system. These, however, are the subject of a number of constraints including, importantly, the process capability to remove reduced sulphur from the treated stream, in one of its oxidation states, and thus linearise the biological sulphur cycle. This remains a major bottleneck in the development of biological wastewater treatment technology. Floating sulphur biofilms are observed as surface layers in numerous aquatic sulphide-rich environments, and it has been suggested that they play a role in the biological cycling of sulphur. The use of sulphur biofilms for the removal of elemental sulphur was identified in this study as a possible means for addressing the technological bottleneck, especially in passive wastewater treatment systems. There is, however, little documented information in the literature on the structure of floating sulphur biofilms, the microbial species responsible for their occurrence or bio-process applications of the system. A linear flow channel reactor was developed to simulate natural conditions and enabled the study of floating sulphur biofilm under controlled laboratory conditions. It was observed that these biofilms developed through three distinct stages termed Thin, Sticky and Brittle films. A microprobe study showed the presence of a steep Redox gradient established across (260 to 380 Î¼m) depth of the floating sulphur biofilm of ~ 0 to -200 mV (top to bottom), which correlated with pH and sulphide gradients across the system. Structural investigations embedded in an exopolymeric matrix containing clearly defined channels and pores. Sulphur crystals were found to develop within the biofilm and above a certain size these disengaged and then settled in the liquid phase below the biofilm. These features, together with the ability of the biofilm to remain suspended at the air/water interface thus provide the surface requirement, and indicate that these structures may be understood as "true" biofilms. In order to study an apparent functional differentiation within the floating sulphur biofilm system, a method was developed to expand its various components over a 13 cm length of agarose tube and across which an oxygen/sulphide gradient was established. This was done by inserting a sulphide plug in the bottom of the tube, overlaying this with the biofilm mixed and suspended in agarose and leaving the tube to open air. After allowing for growth, the different components of the microbial population occurring at various levels across the oxygen/sulphide gradient were sampled. The microbial population was found to resort in distinct functional layers. Aerobes including Acidithiobacillus and Azoarcus, Acidithiobacillus, Thiothrix, Thiovirga and Sulfurimonas were found in the upper oxidised layer. Aerobe and facultative anaerobes such as Chryseobacterium, Bacteroides and Planococcus were found in the middle and heterotrophic anaerobes such as Brevundimonas and uncultured anaerobes were found in the bottom anoxic layer. This enabled the development of a first descriptive structural/functional model accounting for the performance of floating sulphur biofilms. The potential of the floating sulphur biofilm for use as a bioprocess unit operation for sulphide removal in lignocellulose-based low-flow passive systems for acid mine drainage wastewater treatment was investigated. The linear flow channel reactor was scaled up and it was shown that the optimum sulphide removal of 74 % and sulphur recovery of 60 % could be achieved at 20 Â°C. In a further scale up of the linear channel reactor, the floating sulphur biofilm reactor was developed and operated. Sulphide removal and sulphur recovery of 65 and 56 % respectively was measured in the process. An understanding of the nature and function of floating sulphur biofilms and the further development of their potential application in sulphide removal in aquatic systems may provide a useful contribution to the treatment of acid mine drainage and other sulphidic wastewaters.
Keywords: Biofilms; Sulfur; Acid mine drainage -- South Africa; Mine water -- Purification -- Biological treatment; Microbial ecology